2019
DOI: 10.1111/iju.13905
|View full text |Cite
|
Sign up to set email alerts
|

Novel nomogram for the prediction of seminal vesicle invasion including multiparametric magnetic resonance imaging

Abstract: Objectives To create a model that predicts side‐specific seminal vesicle invasion using clinical, biopsy and multiparametric magnetic resonance imaging data. Methods We analyzed data from 544 patients who underwent robot‐assisted radical prostatectomy at a single institution. To develop a side‐specific predictive model, we ultimately considered four variables: prostate‐specific antigen, highest ipsilateral biopsy Gleason grade, highest ipsilateral percentage core involvement and seminal vesicle invasion on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Third, imaging data are unavailable in the SEER database. Two previous investigators (Gandaglia et al 30 and Martini et al 31 ) integrated MRI findings within a nomogram predicting SVI. However, neither investigator relied exclusively on high‐risk PCa patients nor have they provided information on absolute number or specific proportions of high‐risk PCa patients, within their study cohorts 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, imaging data are unavailable in the SEER database. Two previous investigators (Gandaglia et al 30 and Martini et al 31 ) integrated MRI findings within a nomogram predicting SVI. However, neither investigator relied exclusively on high‐risk PCa patients nor have they provided information on absolute number or specific proportions of high‐risk PCa patients, within their study cohorts 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…Two previous investigators (Gandaglia et al 30 and Martini et al 31 ) integrated MRI findings within a nomogram predicting SVI. However, neither investigator relied exclusively on high‐risk PCa patients nor have they provided information on absolute number or specific proportions of high‐risk PCa patients, within their study cohorts 30,31 . Moreover, both studies relied on institutional cohorts with relatively small sample sizes ( n = 504 31 and n = 614 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To diagnose SVI precisely with preoperative information, the nomogram might assist in the accuracy of pT3b. 21 Our level classification was quite simple and required no special instrument for measurement. To assess the level of SVI, the SVs of RP specimens are macroscopically examined and categorized into three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed mpMRI to identify patients at a higher risk of adverse pathology, in addition to conventional clinical parameters 22,23 . Gandaglia et al 22 reported that the combination of mpMRI with accurate biopsy information on MRI-targeted and systematic biopsies improves the accuracy of multivariable models based on clinical and mpMRI data alone.…”
Section: Discussionmentioning
confidence: 99%
“…Gandaglia et al 22 reported that the combination of mpMRI with accurate biopsy information on MRI-targeted and systematic biopsies improves the accuracy of multivariable models based on clinical and mpMRI data alone. In addition, by integrating clinical data with mpMRI information, Martini et al 23 developed a simple model with the low number of variables. They reported that the model performs better at predicting SVI than relying on mpMRI alone; model could be a tool to estimate side-specific SVI.…”
Section: Discussionmentioning
confidence: 99%